OPTIMIZATION OF WATER COOLING SYSTEM FOR SOLAR CELL MODULE - Akkanit, Churairatchinda (Life Sciences and Environment Journal, 2017)
This research aims to increase the efficiency of the solar cells by using water cooling system and optimize water volume for cooling. The cooling system uses the hydraulic ram pump for pumping water into the tank and let water clean solar panel. When the temperature of the 120 watt polycrystalline panel is at 66°C, temperature micro-controller system will spray water to clean the front of solar panel and stops spraying when the solar cell temperature decrease to 40°C. The efficiency of hydraulic ram pump is 65.39%.The maximum power of electronic panel is 78.30 w and efficiency of the panel is 9.00%. There is a significantly high power loss about 1 out of 8 of the maximum power output of the panel.